Making It Happen: Educational Skills, Leadership, and Management Graduates in Actual School Work in the Philippines - S. Arrieta, Gilbert; V. Ancho, Inero; N. Barrameda, Caridad (ASEAN Journal of Education, 2023)
School leaders and teachers take graduate studies to become relevant and better educators. Aside from promotion in their rank, they believe that enrolling in graduate school will develop their skills in their respective fields of specialization. A teacher education university in the Philippines offers graduate programs in educational skill, leadership and management (EDSLM). True to its mission of nurturing innovative teachers and education leaders, many school leaders and teachers in the country are graduates of the university. Recently, enrollment in the masteral and doctoral educational leadership and management program is moderately high which may mean that graduate students believe in the course. Having more graduate students taking EDSLM courses is encouraging but finding if the program prepares effectively and develops holistically the skills of current or future school leaders brings a sense of fulfillment. The aim of this study is to find out the relevance and usefulness of the EDSLM program in terms knowledge and skills, communication skills, human relation skills, leadership skills, research skills, problem-solving skills and information technology skills in their current work. Moreover, the study identifies the needs and challenges of school leadership today and what must be given emphasis in the EDSLM courses. Based on the findings of the study, the graduates agree that the aforementioned skills that they acquired through the program are relevant to a great extent in their current work. They suggested that leadership in the new normal, people skills and technology skills should be given emphasis in the current EDSLM program.